Stormbreaker - Horowitz, Anthony, 1955- (New York : Scholastic Inc., 2002)
After the death of the uncle who had been his guardian, fourteen-year-old Alex Rider is coerced to continue his uncle's dangerous work for Britain's intelligence agency, MI6.
"Published ... by arrangement with Philomel Books, a division of Penguin Putnam Inc."--Verso.
"This edition is only available for distribution through the school market."--P. [4] cover.
First Scholastic printing, February 2002.
670
Keywords: Spies -- Fiction; Terrorism -- Fiction; Orphans -- Fiction; England -- Fiction; Spies -- Fiction; Terrorism -- Fiction; Orphans -- Fiction; England -- Fiction